Proposal for the design of a cultural tourism product. Case: Arboledas, Norte de Santander. - García-Zambrano, María de los Ángeles (Uptc, 2021)
This article presents a research project aimed at designing a cultural tourism product for the municipality of Arboledas in the department of Norte de Santander, as a strategy to promote the community’s social and economic development, based on the tourism objectives at the national, departmental, and municipal contexts. This action research has a qualitative approach. The product design is carried out in four phases: the first is a diagnosis of potentiality; the second is a study of tourism inventories; the third is the establishment of product criteria; and lastly, there is the definition of the action plan. As a result, it is expected to establish a clear route for the entrepreneurs and investors to follow, as well as to promote tourism innovation processes in the territory.